Allergen immunotherapy for IgE‐mediated food allergy: a systematic review and meta‐analysis. Issue 8 (11th May 2017) - Nurmatov, U.; Dhami, S.; Arasi, S.; Pajno, G. B.; Fernandez‐Rivas, M.; Muraro, A.; Roberts, G.; Akdis, C.; Alvaro‐Lozano, M.; Beyer, K.; Bindslev‐Jensen, C.; Burks, W.; et al.
Abstract: Background: The European Academy of Allergy and Clinical Immunology (EAACI) is developing Guidelines for Allergen Immunotherapy (AIT) for IgE‐mediated Food Allergy. To inform the development of clinical recommendations, we sought to critically assess evidence on the effectiveness, safety and cost‐effectiveness of AIT in the management of food allergy. Methods: We undertook a systematic review and meta‐analysis that involved searching nine international electronic databases for randomized controlled trials (RCTs) and nonrandomized studies (NRS). Eligible studies were independently assessed by two reviewers against predefined eligibility criteria. The quality of studies was assessed using the Cochrane Risk of Bias tool for RCTs and the Cochrane ACROBAT‐NRS tool for quasi‐RCTs. Random‐effects meta‐analyses were undertaken, with planned subgroup and sensitivity analyses. Results: We identified 1814 potentially relevant papers from which we selected 31 eligible studies, comprising of 25 RCTs and six NRS, studying a total of 1259 patients. Twenty‐five trials evaluated oral immunotherapy (OIT), five studies investigated sublingual immunotherapy, and one study evaluated epicutaneous immunotherapy. The majority of these studies were in children. Twenty‐seven studies assessed desensitization, and eight studies investigated sustained unresponsiveness postdiscontinuation of AIT. Meta‐analyses demonstrated a substantial benefit in terms of desensitization (risk ratio (RR) = 0.16, 95% CI 0.10, 0.26) and suggested, but did not confirm sustained unresponsiveness (RR = 0.29, 95% CI 0.08, 1.13). Only one study reported on disease‐specific quality of life (QoL), which reported no comparative results between OIT and control group. Meta‐analyses revealed that the risk of experiencing a systemic adverse reaction was higher in those receiving AIT, with a more marked increase in the risk of local adverse reactions. Sensitivity analysis excluding those studies judged to be at high risk of bias demonstrated the robustness of summary estimates of effectiveness and safety of AIT for food allergy. None of the studies reported data on health economic analyses. Conclusions: AIT may be effective in raising the threshold of reactivity to a range of foods in children with IgE‐mediated food allergy whilst receiving (i.e. desensitization) and post‐discontinuation of AIT. It is, however, associated with a modest increased risk in serious systemic adverse reactions and a substantial increase in minor local adverse reactions. More data are needed in relation to adults, long term effects, the impact on QoL and the cost‐effectiveness of AIT.